End-user training of post-graduate students in the use of CD-ROM databases with special reference to the University of the North - Letshela, Phegello Zacharia (University of Limpopo, 1995)
Refer to document
Thesis (M.A) - RAU, 1995
Keywords: End user training; CD-ROM databases; 025.0402857; CD-ROMs - Data processing - Study and teaching